Каталог 2-ї звітної виставки Української державної академії мистецтв (УДАМ). Осінь 1921 року - Білокінь, С. (Студії мистецтвознавчі, 2007)
The published Ukrainian State Academy of Arts Second report exhibition catalogue was composed in 1921 by the known Ukrainian historic of arts Fedir Ernst. It was not published at the time but its manuscript has been preserved till nowadays among the scientist handwritings which we can see now in the Rylsky Institute Scientist archive. A great importance of this document is without doubt. The names of well known artists, then young students of the Academy. We can notice here famous and forgotten names as well. It is of special interest, that master studios and painting’s names are also registered. The critical review of L. Dincess (1922) and the list by V. Pavlovsky add partly this information. From the presented documents we can see haw many names of national artists of the time of 20-th including their creative works were lost. It becomes more clear when we compare these documents with encyclopedic editions as “History of Ukrainian Arts” with Art museum’s catalogues. The conclusion is sad: all we have from that time are only some remains of the general art’s process.